Groupon : does a social commerce superstar have a competitive advantage? - Dhar, Ravi; Smith, Andrea Nagy ([London] : SAGE, 2016)
In June 2011, when Groupon filed for its initial public offering, it was called it 'the cool new kid on the tech block,' and 'the fastest growing company in history.' Groupon was one of a rising generation of internet superstars that were based on social networking. These 'Web 2.0' companies, including Facebook, LinkedIn, and Twitter, used the internet in a new way, not just to publish information in a different medium but to create a business based on user-generated content. This case study discusses this topic.
Originally Published in: Dhar, R., & Nagy Smith, A. (2011). Groupon: Does a Social Commerce Superstar Have a Competitive Advantage? 11-030. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Groupon (Firm); Entrepreneurship -- Case studies; Business planning -- Case studies; Electronic commerce -- Case studies